Injure, honneur et vengeance en Grèce ancienne - Manuela Giordano (Cahiers Mondes Anciens)
This paper explores the way insult, honour, and revenge relate to each other, by the aid of comparative cases (Sarakatzani, Albania, New Guinea), to show that insult, honour, and revenge form a veritable system. Approaching the dispute of Achilles and Agamemnon in the first book of the Iliad, also on the account of the anthropological model of ritual combats, it is further argued that the honour disputed by means of insulting the rival is agonistic. Insult in its turn upholds the function of proving honour as well as the social rules thereby connected, including individual value and identity. The social model of insult resorting from this analysis is conducive to considering it an integral practice of the Homeric world, insofar as the Homeric warrior ‘doer of deeds and speaker of words’ should master a ‘battle rhetoric’ not only in order to persuade and win others’ consent in the assembly, but also to challenge without physical damage his equal by mastering the tool of  insulting words. The paper ends in Athens, where a diachronic perspective is outlined, highlighting how both the Homeric warrior and the Athenian citizen are invited to prove other equals’ honour mastering their aggressive impulse by using insult, and avoiding murderous revenge and physical violence.